2016
DOI: 10.22159/ijpps.2017v9i1.14258
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Vanillin Against Metribuzin-Induced Oxidative Stress and Toxicity in Rats

Abstract: <p><strong>Objective: </strong>Vanillin (Va), a phenolic substance is a natural antioxidant with proven free radical scavenging activity and offers protection against oxidative damage. This study was designed to investigate the ameliorative effect of Va against metribuzin (Mtz) pesticide-induced toxicity and oxidative stress in rats.</p><p><strong>Methods: </strong>Thirty-two rats were equally divided into four groups: control, vanillin (Va), metribuzin (Mtz) and metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The increased levels of urea and creatinine are considered as the marker of impaired kidney functions [27,28]. Thus, in our study, an increase of plasma urea and creatinine reflected the diagnosis of renal damage.…”
Section: Discussionsupporting
confidence: 51%
“…The increased levels of urea and creatinine are considered as the marker of impaired kidney functions [27,28]. Thus, in our study, an increase of plasma urea and creatinine reflected the diagnosis of renal damage.…”
Section: Discussionsupporting
confidence: 51%
“…Similar findings have been found by Ben Saad et al, 46 where vanillin attenuates the increase in lipid peroxidation, AOPP, and protein carbonyl formation in the liver of mice treated with potassium bromate. Also, Kadeche et al 10 have reported that vanillin exhibits hepatoprotective effect against metribyzin pesticide toxicity in male Wistar rats. The improvement of MDA, H 2 O 2 , and AOPP levels after vanillin treatment could be explained by its important role in preventing lipid peroxidation and protecting the integrity of tissues and cells function.…”
Section: Discussionmentioning
confidence: 99%
“…6 It is used against oxidative damage induced by several xenobiotics like pesticides. 6,10 The latters have human serious chronic health effects, including diabetes, respiratory diseases, neurological effects, fetal diseases, genetic disorders, and cancer. 11 14 Among pesticides, maneb is a manganese-containing ethylene-bis-dithiocarbamate fungicide, widely used to control numerous fungal diseases affecting vegetables, fruits, and field crops.…”
Section: Introductionmentioning
confidence: 99%
“…A report provides evidence supporting the potential cardioprotective, antioxidant, and anti-inflammatory effects of coenzyme Q10 against pesticide-induced cardiac toxicity in rats. The findings suggest that coenzyme Q10 supplementation may offer therapeutic benefits in mitigating the adverse effects of pesticide exposure on cardiac health ( 149 ).…”
Section: Protective Effects Of Various Nutraceuticals Against Some Pe...mentioning
confidence: 99%